Antecedents of Perceived Organizational Support to Improve Organizational Commitment in the Public Sector Institutions - Munawar Muchlish (Journal of Accounting Research, Organization and Economics, 2020)
Objective – This study aims to examine the effect of organizational reward, procedural justice, and supervisor support as an antecedent variables of perceived organizational support in increasing organizational commitment as the ultimate dependent variable at the local government units in Serang City Government, Banten Province, Indonesia.  Design/methodology – This research is an empirical study using purposive sampling technique. Data was collected through surveys and the respondents are civil servants from local government unit of Serang City Government. Data analysis was performed with the Structural Equation Model (SEM) with the SmartPLS (Partial Least Square) program. Results – The results of this study provide empirical evidence that organizational reward, procedural justice, supervisor support perceived organizational support, and organizational commitment have a significant positive relationship. This results is consistent with similar studies in private sector.